Genetic variability, phylogeny and functional implication of the long control region in human papillomavirus type 16, 18 and 58 in Chengdu, China - Fang, Liyuan; Lin, Xiaoli; Yang, Yasi; Song, Zhilin; Ding, Xianping; Tan, Liping; Gao, Peng (Virology journal, 2020)
Long control region (LCR) of human papillomavirus (HPV) has shown multiple functions on regulating viral transcription. The variations of LCR related to different lineages/sub-lineages have been found to affect viral persistence and cervical cancer progression differently. In this study, we focused on gene polymorphism of HPV16/18/58 LCR to assess the effect variations caused on transcription factor binding sites (TFBS) and provided more data for further study of LCR in Southwest China. LCR of HPV16/18/58 were amplified and sequenced to do polymorphic and phylogenetic anlysis. Sequences of each type were aligned with the reference sequence by MEGA 6.0 to identify SNPs. Neighbor-joining phylogenetic trees were constructed using MEGA 6.0. Transcription factor binding sites were predicted by JASPAR database. The prevalence of these three HPVs ranked as HPV16 (12.8%) > HPV58 (12.6%) > HPV18 (3.5%) in Chengdu, Southwest China. 59 SNPs were identified in HPV16-LCR, 18 of them were novel mutations. 30 SNP were found in HPV18-LCR, 8 of them were novel. 55 SNPs were detected in HPV58-LCR, 18 of them were novel. Also, an insertion (CTTGTCAGTTTC) was detected in HPV58-LCR between position 7279 and 7280. As shown in the neighbor-joining phylogenetic trees, most isolates of HPV16/18/58 were clustered into lineage A. In addition, one isolate of HPV16 was classified into lineage C and 3 isolates of HPV58 were classified as lineage B. JASPAR results suggested that TFBS were potentially influenced by 7/6 mutations on LCR of HPV16/18. The insertion and 5 mutations were shown effects in LCR of HPV58. This study provides more data for understanding the relation among LCR mutations, lineages and carcinogenesis. It also helps performing further study to demonstrate biological function of LCR and find potential marker for diagnosis and therapy.